Measuring the Quality of Care for Psychological Health Conditions in the Military Health System Candidate Quality Measures for Posttraumatic Stress Disorder and Major Depressive Disorder - Hepner, Kimberly A. (RAND Corporation, 2015)
To inform improvements to the quality of care delivered by the military health system for posttraumatic stress disorder and major depressive disorder, researchers developed a framework and identified, developed, and described a candidate set of measures for monitoring, assessing, and improving the quality of care. This document describes their research approach and the measure sets that they identified.